Jakość dzieciństwa twórczych dzieci 7-9-letnich w perspektywie rodzinnej i lokalnej - Magda-Adamowicz, Marzenna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Thus, the monograph is guided by two objectives: 1) theoretical - I have systematised here knowledge of selected fields and obtained results of my own research, thanks to chich I can develop a rational and effective scientific theory and 2) practical - I have generalised the obtained results of my own research and specified postulates for practice and further scientific research. I undertook the research to describe the family space of creative 7-9 year-old children in certain local environments.
Keywords: dziecko zdolne; nauczanie początkowe; rozwój poznawczy; metody wychowawcze; twórczość; uczniowie; wychowanie w rodzinie; socjologia i społeczeństwo; Polska